Treatment of Patients with Systemic Lupus Erythematosus including Nephritis with Chlorambucil. Issue 5860 (28th April 1973) - Snaith, M. L.; Holt, J. M.; Oliver, D. O.; Dunnill, M. S.; Halley, W.; Stephenson, A. C.
Abstract : Six female patients with systemic lupus erythematosus (S.L.E.) have been treated with chlorambucil. In five the decision was taken after failure by corticosteroids to control progressive renal disease in the face of unacceptable corticosteroid toxicity. After the introduction of chlorambucil renal function improved and all patients remain well six, six, five, three, and two-and-a-half years later, respectively. On renal biopsy five had focal proliferative glomerulonephritis. Repeat biopsy in two cases showed quantitative improvement. The sixth patient was treated with chlorambucil because of failure by corticosteroids to control peripheral vascular lesions and haemolysis and she remains well four years later. In four patients is it probable that amenorrhoea was related to chlorambucil treatment, but there were no other important side effects although one patient developed a degree of marrow depression during treatment. Chlorambucil may hold advantages over the immunosuppressive drugs normally recommended in this condition, azathioprine and cyclophosphamide, as it appears less liable to cause important marrow suppression and, unlike cyclophosphamide is not associated with alopecia and haemorrhagic cystitis.